Beban dengan Koping Keluarga Saat Merawat Pasien Skizofrenia yang Mengalami Perilaku Kekerasan - Jek Amidos Pardede; Laura Mariati Siregar; Merius Halawa (Politeknik Kesehatan Tanjung Karang, 2020)
Schizophrenia is a severe mental disorder that is chronic, reality disorders, cognitive dysfunction, and difficulty in doing activities. Violent behavior is a form of aggressive behavior that causes suffering or hurts others, has an angry response, is expressed by threatening, injuring oneself and others, and can damage the environment. The study aims to determine the relationship of burden with a family coping when treating schizophrenic patients who experience violent behavior in the Prof.Dr.M.Ildrem mental hospital Medan. Descriptive correlation research design with a cross-sectional approach. The entire population of schizophrenic patients who treat family members with violent behavior who undergo outpatient as many as 384 people. Samples totaling 79 people with a sampling technique is a consecutive sampling. The results obtained that the objective burden of the majority family is 74,7% and the subjective burden of the majority family is 60,8%, coping of the adaptive majority family is 97,5%. It is known that there is a strong relationship between burden and family coping when treating patients with schizophrenia who experience violent behavior (p-value=0,000; p-value<0,01) with an objective load value of the correlation coefficient (r)=0,522. And the subjective load coefficient correlation coefficient (r)=0,525. Families are expected to reduce objective and subjective burdens when treating schizophrenic patients who experience violent behavior by increasing adaptive family coping so that the burden in the family is lighter and able to care for family members better.